Role of Audio-Visual Media and its Relationship with Players of Baghdad Directorates' National Teams from Viewpoint of Coaches in Sports and Scouting Activity Departments - Khlood Hameed Abbas (Jurnal Pendidikan Kepelatihan Olahraga: PEJUANG, 2026)
Role of audio-visual media and its relationship with players of Baghdad directorates' national teams from viewpoint of coaches in sports and scouting activity department. Visual and Audio Media Role besides its Relationship with Baghdad Education Directorates' Teams Players from Coaches visions in Sports and Scouting Activities Department. Role of visual and audio media lies in highlighting its relationship with players of education directorates teams from vision of coaches. Visual and audio media in field of sports is one of most prominent and important tools in media system for raising level of national team players.  descriptive approach using an analytical survey method was adopted, as it is suitable for nature of solving research problem.  research population and sample consisted of all coaches in Department of Sports Activities at General Directorate of Physical Education and School Activities in Ministry of Education.  research sample was selected purposively and consisted of (30) individuals. After collecting and processing results, researcher reached following conclusions: Sports media plays a role in conveying activities, message, and goals of national teams to players, contributing to sports education and awareness, highlighting roles of champions, stars, and teams, and indirectly documenting activities. Research reached following conclusions existence of media coverage for educational championships, in addition to effective role in spreading sportsmanship, away from hatred and fanaticism. Audio-visual media helps spread sports culture among members of society. Working on disseminating sports-related information, news, and obstacles. Consolidating sports values, principles, trends, and sustainability. It is clear that every society possesses a value system that determines patterns of sports behavior.